Snack frequency, size, and energy density are associated with diet quality among US adolescents - Gina L Tripicchio; Regan L Bailey; Adam Davey; Christina M Croce; Jennifer Orlet Fisher (Cambridge University Press, 2023)
Abstract Objective: To evaluate snacking and diet quality among US adolescents. Design: Cross-sectional analysis examined snack frequency (snacks/day), size (kcal/snack) and energy density (kcal/g/snack) as predictors of diet quality using the mean of two 24-h dietary recalls. Diet quality was assessed using the Healthy Eating Index (HEI-2015, 0-100), a mean adequacy ratio (MAR, 0-100) for under-consumed nutrients (potassium, fibre, Ca, vitamin D) and mean percentage of recommended limits for over-consumed nutrients (added sugar, saturated fat, Na). Linear regression models examined total snacks, food only snacks and beverage only snacks, as predictors of diet quality adjusting for demographic characteristics and estimated energy reporting accuracy. Setting: 2007-2018 National Health and Nutrition Examination Survey. Participants: Adolescents 12-19 years (n 4985). Results: Snack frequency was associated with higher HEI-2015 (β = 0·7 (0·3), P < 0·05) but also with higher intake of over-consumed nutrients (β = 3·0 (0·8), P ≤ 0·001). Snack size was associated with lower HEI (β = -0·005 (0·001), P ≤ 0·001) and MAR (β = -0·005 (0·002), P < 0·05) and higher intake of over-consumed nutrients (β = 0·03 (0·005), P ≤ 0·001). Associations differed for food only and beverage only snacks. Food only snack frequency was associated with higher HEI-2015 (β = 1·7 (0·03), P ≤ 0·001), while food only snack size (β = -0·006 (0·0009), P ≤ 0·001) and food only snack energy density (β = -1·1 (0·2), P ≤ 0·001) were associated with lower HEI-2015. Conversely, beverage only snack frequency (β = 4·4 (2·1) P < 0·05) and beverage only snack size (β = 0·03 (0·01), P ≤ 0·001) were associated with higher intake of over-consumed nutrients. Conclusions: Smaller, frequent, less energy-dense food only snacks are associated with higher diet quality in adolescents; beverages consumed as snacks are associated with greater intake of over-consumed nutrients.